PENGARUH PERSEPSI SISWA SMA/SMK TENTANG PERAN GURU DAN PROFESI GURU TERHADAP MINAT SISWA MENJADI GURU - Zahara, Rita (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2021)
The purpose of this study is to describe the influence of high school / vocational high school students' perceptions about the role of the teacher and the teaching profession on the interest in becoming a teacher. The population in this study was all students of class XII in FKIP_UNLA partner schools, namely SMAN 8 Bandung, SMAN XI Bandung, SMKN 3 Bandung, and SMK Bandung Community Development, by using quota sampling. This type of research is quantitative research with correlation research methods. Data collection techniques were obtained using: Questionnaire, and interview, namely in the form of statements relating to the perceptions of high school / vocational students about the role of the teacher and the teaching profession the effect on student interest in becoming the teaching profession. Research results show that the perception of high school / vocational students about the role of teachers and the teaching profession contributes effectively to changes in the variable of student interest to become a teacher, and of these two variables the perception of students gives an influence on students' interest in becoming teachers.